2000
DOI: 10.1128/jb.182.8.2163-2169.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Net Charge of the First 18 Residues of the Mature Sequence Affects Protein Translocation across the Cytoplasmic Membrane of Gram-Negative Bacteria

Abstract: This statistical study shows that in proteins of gram-negative bacteria exported by the Sec-dependent pathway, the first 14 to 18 residues of the mature sequences have the highest deviation between the observed and expected net charge distributions. Moreover, almost all sequences have either neutral or negative net charge in this region. This rule is restricted to gram-negative bacteria, since neither eukaryotic nor grampositive bacterial exported proteins have this charge bias. Subsequent experiments performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 46 publications
0
47
0
Order By: Relevance
“…The latter depends on (i) efficiency of peptide translocation, (ii) signal sequence cleavage, and, (iii) recognition by the Ccm complex, and each of these steps may have certain, not necessarily overlapping sequence preferences. For example, cultures producing the shorter 15-mer MP251 resulted in Ϸ10 times more heme peptide than found in cultures producing the longer 17-mer MP312, but the latter had a positive charge close to the N terminus of the mature peptide, a feature that is known to inhibit Sec-dependent translocation (38). The shortest peptide that we found to bind heme, although with a low yield, was the 12-mer QDCLACHHHHHH.…”
Section: Discussionmentioning
confidence: 83%
“…The latter depends on (i) efficiency of peptide translocation, (ii) signal sequence cleavage, and, (iii) recognition by the Ccm complex, and each of these steps may have certain, not necessarily overlapping sequence preferences. For example, cultures producing the shorter 15-mer MP251 resulted in Ϸ10 times more heme peptide than found in cultures producing the longer 17-mer MP312, but the latter had a positive charge close to the N terminus of the mature peptide, a feature that is known to inhibit Sec-dependent translocation (38). The shortest peptide that we found to bind heme, although with a low yield, was the 12-mer QDCLACHHHHHH.…”
Section: Discussionmentioning
confidence: 83%
“…Although several experiments have suggested that the mature proteins are critical for protein export (Tommassen and Kroon, 1987;Simonen et al, 1992;Chen and Nagarajan, 1993;Davis and Model, 1985;Li et al, 1988;Kajava et al, 2000;Gouridis et al, 2009), the precise roles and the property of mature domains are unknown. In this study, we identified the amino acid composition of the mature domains in B. subtilis to study the property of the mature domains that facilitates their export.…”
Section: Discussionmentioning
confidence: 99%
“…These facts suggested that some features of the mature protein played an important role in the protein export process. Indeed, some experimental work has shown that the membrane anchor sequences can block protein export (Davis and Model, 1985) and that the net charge of the NH 2 terminus of the mature sequence affected protein translocation (Li et al, 1988;Kajava et al, 2000). However, the latter rule was restricted to gram-negative bacteria, with no effect on gram-positive bacteria (Kajava et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preprotein export rates within these clusters were related to the magnitude and polarity of the membrane energization states. 18,19 Numerous studies have investigated the influence of SSs either alone or through gene chimeric approaches on the levels of expression, translocation, and secretion. Single point mutations particularly those involving insertion of a charged residue(s) in the hydrophobic core prove to be most deleterious.…”
Section: Introductionmentioning
confidence: 99%